Copper regulation of immune response and potential implications for treating orthopedic disorders - Liu, Yamei; Zhu, Junlang; Xu, Liangliang; Wang, Bin; Lin, Weiping; Luo, Yiwen (Frontiers in Molecular Biosciences, 2022)
Copper is an indispensable trace metal element in human body, and copper deficiency is rare in clinic. However, diseases associated with serum copper deficiency, such as leukopenia, neutropenia, arthritis, osteoporosis, and bone defects, are well known. Copper ions can also achieve the effect of fighting pathogenic bacteria through the "contact killing" characteristic. Copper ion is also an important cofactor of bone matrix synthase, plays an important role in the pathophysiology of orthopedic diseases. The present review highlights the biological functions of copper in immunity, bone diseases and stem cells, as well as potential drug development targeting copper status for diagnostics and therapeutics of copper-associated bone diseases.